(untitled) (Eurasian Journal of Ecology, 2018)
There is a significant change in the organization and development of specially protected natural territories nowadays. The main priority directions of «green» economy are taken into account in the process of their organization and development. The results of the analysis in the article show that methods of total economic value are important at economic evaluation of protected areas, because methods of total economic value are an effective tool in the evaluation of resources, especially in protected natural territories. The article gives a brief description of the specially protected natural territories of the Republic of Kazakhstan. Currently, specially protected natural territories of the Republic are not have only a research and educational interest, but also it’s the single system provider of environmental services as a whole. Thus, within the framework of the green economy methods of economic evaluation of resources of specially protected natural areas have an innovative character and are used in the evaluation of biological resources. Key words: specially protected natural areas, economic evaluation, recreation, value, natural resources,ecosystem services